Influence of stress factors on the vital signs of neonates under intensive care - Barbosa, Robson Ourives; Emmanouilidis, Alessandra; da Silva, Andrea Lúcia Gonçalves; Fleig, Tania Cristina Malezan; Silva, Carolina Barbosa; Cardoso, Dannuey Machado (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and Objectives: Maintenance of regular development and maturation of the CentralNeural System of neonates in the first year of life, associated to the environmental conditions inwhich they are inserted, justifies the scientific relevance of this research. Our objective is todescribe the influence of stress factors on hospitalized neonates in the Neonatal Intensive Care Unitof a teaching hospital. Methods: Cross-sectional study with convenience sampling. The participantswere observed in moments that were identified as being of highest and lowest exposition to stressfactors, thus sound pressure, illuminance, quantity of procedures, presence of pain, and theindicators of vital signs expressed by the patients’ monitors were registered. Results: Thirteenneonates, predominantly moderate premature babies of low weight, of c-section birth, average ageof 8.0 ± 5.9 days, mostly female and breathing room air, were evaluated. We noted that stressfactors produced significant increase of the heart rate (sound pressure: p=0.001, illuminance:p